Serological and molecular screening for zoonotic pathogens among wild hedgehogs (Erinaceus europaeus) from urban areas of Poland - Turlewicz-Podbielska Hanna; Ruszkowski Jakub Jędrzej; Pisarek Maria; Adaszek Łukasz; Pomorska-Mól Małgorzata (Journal of Veterinary Research, 2025)
Wild European hedgehogs (Erinaceus europaeus) can carry various pathogens potentially harmful to humans. This study was conducted to determine the occurrence of selected zoonotic pathogens in European hedgehogs from urban areas of central-western Poland.